Bhumji Grammar - Ramaswami, N. (My University, 1992)
This book is a Bhumji Grammar consisting of 7 Units on learning about Introduction, Phonetic Description of Bhumij Sounds, Phonological Description, Sandhi, Morphology, Verb, Word-Formation, Syntax, and Text.
Keywords: Bhumij